2014
DOI: 10.1097/qad.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Serological response to 13-valent pneumococcal conjugate vaccine in children and adolescents with perinatally acquired HIV infection

Abstract: Background:Children with perinatally acquired HIV (paHIV) remain at an increased risk of pneumococcal infection despite highly active antiretroviral therapy (HAART). Beyond infancy, responses to pneumococcal conjugate vaccine (PCV) remain under-investigated. There are currently no published data on serological response to 13-valent PCV (PCV13) in the HIV-infected populations.Methods:We measured pneumococcal serotype-specific IgG in 48 paHIV-infected child patients (CP), 27 young adult healthy controls (AHC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…Immune response in HIV+ children and adolescents has also been assessed for 13-valent PCV; children with perinatally-acquired HIV had mounted robust serotype-specific IgG responses 1 month after a single 13-valent PCV dose, persisting up to 6 months for most serotypes. [19] …”
Section: Discussionmentioning
confidence: 99%
“…Immune response in HIV+ children and adolescents has also been assessed for 13-valent PCV; children with perinatally-acquired HIV had mounted robust serotype-specific IgG responses 1 month after a single 13-valent PCV dose, persisting up to 6 months for most serotypes. [19] …”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies use levels of antigen-specific antibodies as an index to evaluate vaccine efficacies. Among these studies, ART has been found to improve humoral immune responses to vaccination in HIV-infected individuals, especially in patients with viral suppression and higher CD4+ T cell counts [93-95]. Nevertheless, frequencies of antigen-specific memory B cells against measles vaccine are not increased in children after 5 years of ART [90], suggesting that ART alone may be incapable of restoring the depletion of antigen-specific memory B cell pools.…”
Section: Effect Of Art On Memory B Cell Perturbationsmentioning
confidence: 99%
“…Although we tried to study children under 7 years of age, which was referred to as a homogeneous age group in previous studies 36,37 , our results showed that the age group can affect the efficacy and effectiveness of vaccines in both HI and HUI children. Although the study results showed that older HI children had the lowest efficacy compared to children under 2 years old, this result may be due to the length of follow-up time (around 6 years VS less than 2 years) and is not an follow-up adjusted valuable result 38 .…”
Section: Discussionmentioning
confidence: 98%